Research on The Application of Mind Mapping in Indonesian-Chinese Character Teaching Review Lesson: A Case Study of The Department of Chinese Language and Culture Universitas Sebelas Maret 心智导图在印尼汉字教学复习课中的应用研究——以 三一一大学中文系为例 - Stephanie Phanata (Sinolingua: Journal of Chinese Studies, 2023)
In order to probe the application of mind mapping in the Indonesian Chinese character teaching review lesson, the author attempts to use mind mapping to promote the development of student's writing skills in the Chinese character teaching review lesson. The research object of this article is a junior class student in the Department of Chinese Language and Culture of Universitas Sebelas Maret (first semester, newly exposed to Chinese) 180 mind maps were collected from 90 students and drawn. The analysis results of the observation method, action method, and questionnaire survey method indicate that Chinese character mind mapping is helpful in improving Indonesian students' ability to master Chinese characters and improve their quality and interest in Chinese character learning during the review lesson. When using mind mapping, teachers should try to highlight their strengths and avoid weaknesses. With the popularization of computers and the rapid development of graphic technology, the application of mind maps in Chinese character teaching as a foreign language will gradually be recognized, indicating that the development prospects of mind maps are bright.